2015
DOI: 10.1021/acsnano.5b02997
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Differentiation of Therapeutic Insulin-Producing Cells from Bone Marrow Cells via Extracellular Vesicle-Mimetic Nanovesicles

Abstract: The current diabetes mellitus pandemic constitutes an important global health problem. Reductions in the mass and function of β-cells contribute to most of the pathophysiology underlying diabetes. Thus, physiological control of blood glucose levels can be adequately restored by replacing functioning β-cell mass. Sources of functional islets for transplantation are limited, resulting in great interest in the development of alternate sources, and recent progress regarding cell fate change via utilization of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 49 publications
2
76
0
Order By: Relevance
“…Although EVMs exhibit characteristics extremely similar to Exos,53, 54, 124 the actual identity of EVMs needs to be clarified by further investigation.…”
Section: High‐yield Tactics: Extracellular Vesicle‐mimetic Nanovesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EVMs exhibit characteristics extremely similar to Exos,53, 54, 124 the actual identity of EVMs needs to be clarified by further investigation.…”
Section: High‐yield Tactics: Extracellular Vesicle‐mimetic Nanovesiclesmentioning
confidence: 99%
“…Furthermore, it has gradually been revealed that EVMs show similar properties to EVs;53, 54 therefore, the method of producing EVMs might be a much more effective way to manufacture modularized EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, functional studies showed that the nanovesicles directed bone marrow cell differentiation into insulin-producing cells in vitro, that when transplanted into diabetic mice, were capable of controlling blood glucose levels for 60 days. Though no control comparison was made to native EVs derived from the same β-cell line, a yield of 8.2 × 10 8 particles per 1 µg of total protein was reported, confirming that generally a high number of vesicles can be made from this method [105]. A similar protocol was used to produce EV mimics from human breast epithelial cells [106].…”
Section: Cell-derived Nanovesiclesmentioning
confidence: 99%
“…As such, it is especially remarkable when authors showed that synthetic EVs were able to be produced at about a 100-fold greater yield than native EVs secreted by the same number of cultured cells. Similar methods were used to synthesize EV-mimicking nanovesicles from pancreatic β-cells in which cells were harvested and serially extruded through 10, 5 and 1 μm pore-sized polycarbonate membrane filters [105]. Assessment of the physical properties of nanovesicles revealed an average size of 203 nm, and it has been found that protein contents similar to donor cells though insulin and Pdx1, a transcription factor that regulates β-cell development, were not detected.…”
Section: Cell-derived Nanovesiclesmentioning
confidence: 99%
“…Based on this concept, siRNA or miRNA could be loaded in cells, and then, the RNA would be capsulated in EVs during their formation in culture media. Another loading strategy is to mix or incubate drugs with cells, and drug-loaded vesicles could be obtained by extrusion of cells (47) (48) (42). Jang’s group (47) produced doxorubicin-loaded nanovesicles by serial extrusions of cells via a membrane filter, and drug-loaded vesicles were purified using a series of density gradient centrifugations.…”
Section: Loading Therapeutics In Evsmentioning
confidence: 99%